POTENTIAL DEVELOPMENT (Qalb/Ø§Ù„Ù‚Ù„Ø¨,Aql/Ø§Ù„Ø¹Ù‚Ù„ ,Fuad/Ø§Ù„ÙØ¤Ø§Ø¯ , A'yun/Ø§Ø£Ù„Ø¹ÙŠÙ† ,Al-Adhan'/ Ø§Ø£Ù„Ø°Ø§Ù†) IN THE CONTEXT OF THE QURAN - Nahrim Ajmain; Syafril Syafril (Program Studi Ilmu Al-Qurâ€™an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2023)
Humans are creatures that Allah has created in the best condition and form, but what makes humans noble is due to their faith and piety. For this reason, in this study the author will discuss some of the potentials that cause faith and piety to always exist and grow in humans. The potential that the author refers to in this study is the potential of Qalb, 'Aql, Fu'ad and its correlation with the potential of Sense which Allah bestowed on humans in the context of developing educational potential in human life. According to the Quran, the human senses consist of three parts, namely the outer, inner, and inner senses. Meanwhile, according to conventional psychology, there are only two kinds of senses, namely the outer and inner senses. In addition, the Quran holds that the senses should not only function to absorb information and form knowledge, but must also be able to form beliefs.